2020
DOI: 10.1111/jofo.12338
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of food‐caching site preferences in young Florida Scrub‐Jays: evidence of learning or changing social status?

Abstract: Florida Scrub‐Jays (Aphelocoma coerulescens) are cooperative breeders endemic to Florida’s oak scrub. In autumn, Florida Scrub‐Jays cache thousands of acorns and exhibit behaviors that appear to balance cache site selection against food degradation or cache robbery. However, both experience and position within a social dominance hierarchy could affect individual cache preferences. We examined the cache site preferences of birds with differing levels of caching experience and at different strata within a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that caching species, particularly corvids, can actively use aspects of their environment to aid in preserving caches. For example, Florida scrub‐jays ( Aphelocoma coerulescens ) select for high‐tannin acorns and will cache in and relocate acorns to drier sites less vulnerable to degradation and germination (Fleck & Woolfenden, 1997; Fuirst et al, 2020; Kulahci & Bowman, 2011). Additionally, spotted nutcrackers ( Nucifraga caryocatactes ) also select cache‐sites with favourable microclimatic conditions (Neuschulz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that caching species, particularly corvids, can actively use aspects of their environment to aid in preserving caches. For example, Florida scrub‐jays ( Aphelocoma coerulescens ) select for high‐tannin acorns and will cache in and relocate acorns to drier sites less vulnerable to degradation and germination (Fleck & Woolfenden, 1997; Fuirst et al, 2020; Kulahci & Bowman, 2011). Additionally, spotted nutcrackers ( Nucifraga caryocatactes ) also select cache‐sites with favourable microclimatic conditions (Neuschulz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%